The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2478/raon-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk based on adapted IBIS prediction model in Slovenian women aged 40–49 years - could it be better?

Abstract: AbstractBackgroundThe aim of the study was to assess the proportion of women that would be classified as at above-average risk of breast cancer based on the 10 year-risk prediction of the Slovenian breast cancer incidence rate (S-IBIS) program in two presumably above-average breast cancer risk populations in age group 40-49 years: (i) women referred for any reason to diagnostic breast cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…And the incidence of BC in France is the highest in Europe (Sancho-Garnier and Colonna, 2019). In Asian countries, the incidence rate of BC has also been increasing rapidly (Mubarik et al, 2020;Oblak et al, 2020). The pathogenesis of BC is multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…And the incidence of BC in France is the highest in Europe (Sancho-Garnier and Colonna, 2019). In Asian countries, the incidence rate of BC has also been increasing rapidly (Mubarik et al, 2020;Oblak et al, 2020). The pathogenesis of BC is multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded, that inclusion of additional risk factors into the S-IBIS is needed to reliably stratify women into the BC risk groups. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Some regional and hospital/breast cen- tres-based research have been conducted to assess women's BC risk. 19,25,31,32 Due to different subpopulations assessed and low sample volumes, the results of these studies cannot be directly compared to our study. They were all conducted among women referred to breast centres, where women with a positive family history or previous biopsies are normally assessed.…”
Section: Risk Stratification and Comparison With Other Studiesmentioning
confidence: 91%
See 2 more Smart Citations